In situ polymerization process: an essential design tool for lithium polymer batteries dagger - Vijayakumar, Vidyanand; Anothumakkool, Bihag; Kurungot, Sreekumar; Winter, Martin; Nair, Jijeesh Ravi (Energy & Environmental Science, 2021)
Polymer electrolytes (PEs), a type of solid-state electrolytes (SSEs), have been in contention for nearly half a century to replace organic liquid electrolytes (LEs) that are used in state-of-the-art lithium-ion batteries (LIBs). They are envisaged to accelerate the industrial-scale production of safe, energy-dense, flexible, and thin lithium polymer batteries (LPBs). LPBs are expected to be widely employed for electric propulsion and other futuristic applications, such as flexible electronics and the Internet of Things (IoT). Even though several polymer architectures and chemistries have been attempted so far, PEs that can outperform LEs remain a real challenge. Apart from inadequate Li+-ion transport properties, challenges concerning the integration of PEs and the engineering of compatible, robust, and durable interfaces and interphases at both the electrodes of LPBs must be appropriately addressed. Recently, the in situ polymerization process has been widely employed as a robust fabrication tool for surpassing the intricacies related to the integration of PEs in LPBs. Hence, in this review, we focus on the in situ polymerization processes that employ various polymerization methods (e.g., free-radical polymerization, ionic polymerization, electropolymerization, condensation polymerization, etc.), functional monomers and oligomers (e.g., acrylate, methacrylate, allyl and vinyl ethers, epoxides, etc.), and PE integration strategies for the fabrication of lithium (ion and metal) polymer batteries (LIPBs and LMPBs). Additionally, this review also evaluates the approaches that have been developed until now to implement the in situ processing of LPBs from large-sized pouch cells to flexible-/printable-batteries and even microbatteries.